Relation between cognitive impairment and early death in the elderly. - Eagles, J M (1990)
STUDY OBJECTIVE--To study the association between cognitive impairment and early death in elderly patients living in the community. DESIGN--Case-control study of 410 patients assessed by the mental status questionnaire and followed up after three years. SETTING--A general practice in Inverurie, Aberdeenshire, with 14,000 patients. PATIENTS--205 Patients aged greater than or equal to 65 with cognitive impairment according to the mental status questionnaire (score less than or equal to 8) and 205 patients scoring greater than 8 on the questionnaire matched for age and sex. MAIN OUTCOME MEASURE--Death. RESULTS--The relative risk of death in the cognitively impaired patients overall was 3.5. Those patients who scored less than or equal to 7 on the mental status questionnaire were five times more likely to die than their controls. There was no difference in risk of death between those with severe or moderate cognitive impairment. CONCLUSIONS--Cognitive impairment is associated with early death.